Evaluating the Implementation of a Medication Dispensing Telehealth Platform in Community Behavioral Health Settings. - Mattocks, Nicole; Swenson, Naomi; Consol, Amanda; Phillips, Hilary; Hopkins, Karen; Siegel, Jennifer L.; Manleigh, Caitlin; Unick, Jay (Community Mental Health Journal, 2026)
Individuals with serious mental illness (SMI) often require ongoing medication managed through intensive community-based service delivery (IC-BSD) programs. While these programs support the SMI population, they face challenges with efficiency and effectiveness. Innovative technological solutions like the Medherent™ telehealth platform, which automates medication dispensing and tracks adherence, offer potential improvements. However, research on their use in SMI populations and implementation barriers in community settings is limited. This study examines the implementation of Medherent™ to support medication management in community mental health settings. Using a mixed-methods approach, we assessed the appropriateness, acceptability, adoption, and feasibility of Medherent™. The Work Observation Method by Activity Timing (WOMBAT) was employed to quantify medication management tasks in three community mental health agencies, and qualitative interviews with 28 staff members were conducted. Results suggest that Medherent™ can save up to 7.35 h of staff time per client each month, enabling staff to focus on higher-value rehabilitation activities. Staff generally found Medherent™ acceptable, reporting increased efficiency and enhanced client independence. However, challenges included technical issues such as power outages, Wi-Fi connectivity, and the need for ongoing staff training. This study emphasizes the importance of organizational readiness and effective communication between agencies and pharmacy providers for successful implementation. Future research should explore broader impacts on clinical outcomes and assess the telehealth platform's long-term feasibility.